Impact of molecular architecture of chain extenders on the morphology of chain-extended polyamide 6 - Goh, Cher Hao (Nanyang Technological University, 2022)
Polyamide 6 has a wide number of uses, after degradation, the number of uses will decrease and create more waste. Chain extension is a good way of recycling polyamide 6 and is a solution that has been explored for many years. There are still some limitations with the current implantation of chain extension as a recycling method and this project will be a supplement to that. In this project, Polyamide 6 is chain extended with 7 different additives all of which has the same functional group, with differing molecular architectures. The resulting chain extended samples will be studied with isothermal DSC, dynamic DSC, and small angle x-ray scattering (SAXS). These tests will allow for the comparison of the crystal kinetics and morphology of polyamide 6 before and after chain extension with different chain extenders. The main comparisons will be about the molecular weight of the extender, the present side groups such as benzene and also the degree of branching present.